2022
DOI: 10.12998/wjcc.v10.i18.6141
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous infection caused by Mycobacterium abscessus following cosmetic injections of botulinum toxin: A case report

Abstract: BACKGROUND In recent years, the cosmetic intervention related infections caused by nontuberculous mycobacteria (NTM) are increasing as the informal cosmetic treatments are performed. However, many dermatologists are inexperienced in the diagnosis and management of similar cases. Here we report a case of subcutaneous infection caused by Mycobacterium abscessus ( M. abscessus ) following cosmetic injections of botulinum toxin. CASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…A total of 24 cases across 18 studies of cutaneous NTM infection after cosmetic injections reported from 2013 to 2023 were identified in the search 4–21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 cases across 18 studies of cutaneous NTM infection after cosmetic injections reported from 2013 to 2023 were identified in the search 4–21 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 cases across 18 studies of cutaneous NTM infection after cosmetic injections reported from 2013 to 2023 were identified in the search. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The characteristics of the included studies are summarized in Table 1. The majority of the patients were female (23 out of 24 patients), with ages ranging from 28 to 56 years old.…”
Section: Results Of Literature Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation